A study on the prevalence of methicillin resistant Staphylococcus aureus (MRSA) in clinical samples of Baghdad hospital - Ahmad Hassan chaloob (African Journal of Advanced Pure and Applied Sciences, 2022)
The serious nosocomial illness, Methicillin-resistant Staphylococcus aureus, which is spreading across hospitals and the general populace in Iraq, is a major problem. The goal of our research was to figure out how common MRSA was in the province of Baghdad's hospitals and community settings. A total of 150 clinical samples were processed over the course of three months. Two different antibiotic susceptibility tests were done on the MRSA that was found, and the results were analyzed using CLSI 2019 guidelines. . -lactamase production was discovered utilizing phenotypic techniques. The findings showed that 55 of the 150 samples collected from various clinical regions were positive for Staphylococcus spp. On the other hand, PCR was used to determine whether mecA was present in the 30 isolates. Ten isolates had the 533 bp mecA-specific PCR result.